Artemis Fowl. The opal deception : the graphic novel - Colfer, Eoin (Colfer, Eoin. Artemis Fowl, 2014)
After his last run-in with the fairies, Artemis Fowl's mind was wiped of memories of the world belowground and any goodness grudgingly learned is now gone with the young genius reverting to his criminal lifestyle.